Analysis of Structural Calculations of Pile Foundations on Bridge Abutment Working, BLOKANG, Serang Regency, Banten Province - Simon Petrus Simorangkir; Diana Suita; Johan Oberlyn Simanjuntak (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
The abutment planning on the Blokang bridge, Serang Regency, Banten Province, resulting in the calculation of bearing capacity based on physical and mechanical properties data from laboratory tests, on the results of the BH4 right abutment with 60 cm diameter piles, the bearing capacity Qu = 248,683.58 kg, while for the left BH support -1 is obtained Qu = 244.186.99kg., And taking into account the value of the N-SPT soil investigation on the right abutment BH-4 is obtained Qu = 261,680.45 kg and the N-SPT soil investigation on the left abutment BH-1 is obtained Qu = 335,674.28 kg . The cause of Qu is based on SPT field test data, where the right abutment is N-SPT = 21, while the left abutment is N-SPT 28. The greater the value of N-SPT = 28, the soil is better, stronger soil, harder